University Students’ Reading Habits Through Their Use of Libraries: A Qualitative Study - Acharya, Milan; Acharya, Kamal Prasad (Access: An International Journal of Nepal Library Association, 2025)
This study examines university students’ reading habits with a focus on library use at Tribhuvan University, Nepal. The purpose was to understand how master’s level students engage with the library for academic and personal learning needs. A qualitative research design was applied. Data was collected from fifteen Master-level students through in-depth interviews, each lasting around forty minutes. Verbatim transcription and thematic analysis were employed to interpret the data. Findings reveal that students primarily use the library during free periods, for preparing notes, conducting research, and reviewing materials for final examinations. The library is perceived as a supportive learning environment that enhances concentration and provides access to essential academic resources. However, irregular use of the library was also noted, often influenced by busy schedules and availability of digital resources. The study highlights the continued relevance of the university library in developing reading habits, despite growing digital alternatives. It concludes that libraries not only support exam preparation but also foster self-study and academic discipline. Recommendations are made to improve library facilities and promote regular reading practices among students.